2015
DOI: 10.3892/or.2015.4383
|View full text |Cite
|
Sign up to set email alerts
|

The differentiation of hMSCs counteracts their migration capability and pro-angiogenic effects in vitro

Abstract: Human mesenchymal stem cells (hMSCs) have been applied therapeutically in numerous clinical trials. The pro-angiogenic effects of hMSCs, as well as their strong tumor tropism, have been shown both in vitro and in vivo. Some studies suggest using hMSCs as potential drug-carriers for tumor therapy. In previous investigations by our group, the pro-tumorigenic effects of hMSCs on head and neck squamous cell carcinoma (HNSCC) were shown. However, the influence of hMSCs on tumor vascularization as well as the possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 46 publications
1
4
0
1
Order By: Relevance
“…In addition, the in vitro and in vivo migration capacity of DPSCs towards the FaDu HNSCC cell line was evaluated. As previously demonstrated for BM-MSCs (49,(66)(67)(68), FaDu cells displayed a signi cant chemoattractant effect on DPSCs in an in vitro transwell migration assay. Different administration routes have already been applied to test the in vivo tropism of MSCs towards cancer cells.…”
Section: Discussionsupporting
confidence: 75%
“…In addition, the in vitro and in vivo migration capacity of DPSCs towards the FaDu HNSCC cell line was evaluated. As previously demonstrated for BM-MSCs (49,(66)(67)(68), FaDu cells displayed a signi cant chemoattractant effect on DPSCs in an in vitro transwell migration assay. Different administration routes have already been applied to test the in vivo tropism of MSCs towards cancer cells.…”
Section: Discussionsupporting
confidence: 75%
“…The osteogenic environment is associated with differentiated MSCs, HUVECs, and OIM. Studies have shown that many factors have a negative effect on the angiogenesis of HUVECs, including differentiated MSCs and OIM [8][9][10]. However, it is still unknown which components in OIM inhibit the angiogenesis of HUVECs.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, LIPUS with spatially averaged and temporally averaged (SATA) intensity of 30 mW/cm 2 was applied to hMSCs cultured in basal or osteogenic medium at different experimental time points. The MSC differentiation response to shortand long-term LIPUS stimulation was analyzed in terms of (a) changes in the expression of protein markers, through MS-based quantitative proteomic technologies, in order to identify protein networks; and (b) the modulation of different stem cell markers (CD73, CD90, CD105, OCT-3/4, NANOG, SOX2) and osteogenic pathways; both activated by LIPUS (Kuhn & Tuan, 2010;Liu & Lee, 2014;Pricola, Kuhn, Haleem-Smith, Song, & Tuan, 2009;Scherzed et al, 2016;Yoon et al, 2014).…”
mentioning
confidence: 99%